The principle of prudence in public sector accounting—a comparative analysis of cautious and asymmetric prudence. Issue 7 (3rd October 2022) - Adam, Berit; Heiling, Jens; Meglitsch, Tim
IMPACT: The principle of prudence plays a significant role in the design of the EPSAS. In Germany it has been argued that a lack of consideration of the principle of prudence in the IPSASB's Conceptual Framework and in the IPSAS mean that IPSAS are not an ideal reference framework for the EPSAS. Based on a comparative analysis of the IPSAS principle of prudence and the principle of prudence as it is applied in the German Standards of Governmental Accrual Accounting the authors examine the role and the design of the principle of prudence within public sector accounting systems. The findings of this article will be of value to national and international public sector accounting standard-setters. ABSTRACT The draft EPSAS Conceptual Framework proposes the prudence principle as a qualitative characteristic of financial reporting. Limited academic debate has taken place on the role of the prudence principle in public sector accounting. This article critically discusses the principle of prudence with its antagonistic interpretations 'cautious prudence' and 'asymmetric prudence' and its role in the design of public sector accounting in the context of the emerging EPSAS.